Single photon triggered dianion formation in TCNQ and F4TCNQ crystals - Ma, Lin (2017)
Excited state dynamics in two strong organic electron acceptor systems, TCNQ and F4TCNQ single crystals, was studied. After absorption of a single photon, dianions are formed in both crystals on ultrashort timescale. By use of transient absorption spectroscopy, we demonstrate that the dianion formation in F4TCNQ is mediated by the radical anion precursor which is described by a two-step model. Our measurements show the phenomenon that in this quinoid acceptor crystals in the absence of additional donor molecule, it is possible to resolve the two step formation of a doubly charged anion upon absorption of a single low energy photon (2.6 eV).